2021
DOI: 10.3389/fnins.2021.711542
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Dorsolateral Prefrontal Cortex Glutamate/Glutamine Levels Following Repetitive Transcranial Magnetic Stimulation in Young Adults With Autism

Abstract: Altered excitatory and inhibitory neurotransmission has been implicated in autism spectrum disorder (ASD). Interventions using repetitive transcranial magnetic stimulation (rTMS) to enhance or inhibit cortical excitability are under study for various targets, though the mechanistic effects of rTMS have yet to be examined in ASD. Here, we examined whether an excitatory rTMS treatment course modulates glutamatergic (Glx) or γ-aminobutyric acid (GABA) metabolite levels in emerging adults with ASD. Twenty-eight pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 75 publications
0
17
0
Order By: Relevance
“…With respect to TMS trials, three trials stimulated posterior superior temporal sulcus (pSTS) with one unilaterally ( 27 ) and two bilaterally ( 29 , 30 ). Two trials chose to intervene over bilateral DLPFC ( 26 , 28 ), and one focused on bilateral dorsomedial prefrontal cortex (dmPFC) ( 21 ) ( Table 3 ). Similarly, TMS at 50 Hz with 600 pulses in total, namely intermittent theta burst stimulation (iTBS), was given to the participants in those trials focused on pSTS ( 29 , 30 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to TMS trials, three trials stimulated posterior superior temporal sulcus (pSTS) with one unilaterally ( 27 ) and two bilaterally ( 29 , 30 ). Two trials chose to intervene over bilateral DLPFC ( 26 , 28 ), and one focused on bilateral dorsomedial prefrontal cortex (dmPFC) ( 21 ) ( Table 3 ). Similarly, TMS at 50 Hz with 600 pulses in total, namely intermittent theta burst stimulation (iTBS), was given to the participants in those trials focused on pSTS ( 29 , 30 ).…”
Section: Resultsmentioning
confidence: 99%
“…Given these two tasks, nonetheless, are not specific to the pSTS activities, they also adopted the repetitive behavior scale-revised (RBS-R) as the exploratory outcome ( 30 ). Interestingly, both Liu et al and Moxon-Emre et al showed interest in the objective outcome, thereby fMRI and GlX and GABA level was applied for outcome assessment ( 27 , 28 ). A different set of scales including BRIEF-MCI and the Cambridge Neuropsychological Test Automated Battery (CANTAB) task were adopted by Ameis et al ( 26 ).…”
Section: Resultsmentioning
confidence: 99%
“…Reliable biomarkers of SI in ASD youth and young adults may help identify at-risk individuals, with plausible utility for treatment planning (i.e., predicting potential for treatment response) and tracking neurobiological responses to interventions. We recently found that bilateral rTMS to DLPFC modulates Glx levels in the left DLPFC (MRS data were not collected from the right DLPFC) and that baseline Glx predicted change in Glx from pre- to post-rTMS in the same ASD sample included here [ 15 ]. There is evidence that excitatory rTMS alters the glutamatergic system [ 16 , 17 , 18 ] and may normalize NAA levels in treatment-resistant depression [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Participants: Twenty-eight ASD youth and young adults (mean (SD) = 23.3 (4.69) years, range 16–33 years, 21 male/7 female assigned at birth) underwent 1 H-MRS scans during a baseline assessment of our recently completed repetitive transcranial magnetic stimulation (rTMS) clinical trial (Clinicaltrials.gov; ID: NCT02311751) [ 15 , 20 , 21 ]. The present sample is identical to the baseline ASD sample from Moxon–Emre et al (2021), wherein we detail specifics pertaining to final sample selection, including quality control (QC) of 1 H-MRS data used here.…”
Section: Methodsmentioning
confidence: 99%
“…For glutamate and GABAergic circuits that are abnormal in ASD, one study found that rTMS (1 Hz) treatment for 2 weeks effectively alleviated the acquired autistic-like symptoms in a rat model by regulating synaptic GABA transmission ( 65 ). Furthermore, in adults with ASD, one study found that rTMS to the DLPFC may modulate local glutamate levels ( 66 ).…”
Section: Discussionmentioning
confidence: 99%